Analisis Faktor-Faktor yang Mempengaruhi Keputusan Mahasiswa UIN Sunan Gunung Djati Bandung dalam Menggunakan E-Wallet - Mia Lasmi Wardiyah; Zenny Pebrianti; Arif Budiman; Amia Putri Rafiani; Fauzy Abdurrohman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the factors that influence students of UIN Sunan Gunung Djati Bandung in deciding to use e-wallets as a means of digital payment. The rapid growth of cashless transactions among young users has raised questions about what drives their adoption of digital financial services. Using a descriptive qualitative approach, the research involved 30 third-semester students of the Sharia Accounting Study Program selected through purposive sampling. Data were collected through open-ended questionnaire items distributed via Google Forms, allowing respondents to describe their experiences, motivations, and perceptions regarding e-wallet usage. The findings show that the level of e-wallet utilization among students is notably high, with DANA emerging as the most widely used application. Students’ decisions are influenced mainly by ease of use, fast transaction processes, promotional offers, and social encouragement from peers. Perceptions of security are generally positive, supported by features such as PIN and OTP verification, although several respondents still expect improvements to prevent data breaches. Students also view e-wallets as more practical for small, daily transactions, while digital banking services are considered more suitable for saving or conducting larger transactions. Overall, the study highlights that e-wallets play a significant role in shaping students’ financial behavior by offering convenience, efficiency, and accessible digital financial tools that align with their everyday needs.